Effect of PbS Thin Film Thickness with Cu-Doping on Thermoelectric Properties Using Spin Coating Method - Reza Akbar Pahlevi; Hari Rahmadani; Markus Diantoro (Universitas Negeri Malang, 2022)
A thermoelectric device is produced from several materials that can convert heat into electrical energy or vice versa by generating the Seebeck effect and the Peltier effect. Then the energy can be formed from a heat source. This research used copper monosulfide (CuS) and lead monosulfide (PbS) as the primary materials for thermoelectric manufacture in the form of films. The method used in this research is a spin coating. This method uses the procedure of making a thin film on the substrate. The choice of this material is because CuS and PbS have high electrical conductivity and low thermal conductivity, so the value figure of merit (ZT) is high. From the thin film produced, an annealing process will be carried out to remove unwanted elements. After the sample is finished, the electrical conductivity test will be carried out with four probes, x-ray diffraction (XRD), and scanning electron microscopy (SEM). The four probes' conductivity test characterization results for one-layer, two-layers, and three-layers variations are 27.4 S/m, 53.6 S/m, and 106.8 S/m, respectively. From the SEM results, the grain size obtained from one-layer, two-layers, and three-layers variations are 227.9 nm, 397.8 nm, and 269.6 nm, respectively. Based on the XRD results, the crystal size obtained for variations of one-layer, two-layers, and three-layers has a size of 43.65 nm, 43.55 nm, and 43.60 nm, respectively. Furthermore, the lattice parameter has the same value from each sample variation, which is 5.93 Å.DOI: 10.17977/um024v7i22022p062